The role of adipokines and ghrelin in interactions and clinical implications in childhood obesity - Karrar Haider Haddawi; Ahmed Ghdhban Al-Ziaydi; Fatima Abd Al-Kathem Al-Khalidi (Journal of Education and Health Promotion, 2024)
BACKGROUND: Childhood obesity is a growing global health concern, especially prevalent in the Arabian Peninsula, and is known to contribute to metabolic syndrome and insulin resistance. This study aimed to investigate the interplay between adipokines (leptin and adiponectin), ghrelin, and insulin homeostasis in childhood obesity. MATERIAL AND METHODS: A case–control study was conducted in Babylon involving 120 children/adolescents (7–17 years). The participants were divided into two groups: 60 obese and 60 healthy controls. Anthropometric and biochemical measures were examined, applying World Health Organization (WHO) growth standards to categorize weight status. Data on blood lipids, glucose, adipokines, and ghrelin were collected in Babylon (Merjan Medical City), ensuring accuracy and providing insights into pediatric obesity’s metabolic and hormonal status. RESULT: Clinical, anthropometric, and laboratory attributes of children were evaluated, with classification as normal-weight or obese based on BMI/Z-score and Waist Circumference. The obese group exhibited elevated triglycerides and insulin levels, as well as reduced adiponectin levels (P ≤ 0.001). Leptin levels showed a positive correlation with BMI/Z-score (r = 0.352, P = 0.006). A diagnostic model demonstrated the significant diagnostic capacity of leptin (AUC > 99%) and its importance in predicting childhood obesity. Each unit increase in leptin elevated the probability of obesity by a factor of 1.197 (95% CI: 1.0507–1.3632, P = 0.0068). CONCLUSION: The study revealed significant differences in clinical, biochemical, and biological markers of obesity between the research groups and the control group. Leptin emerged as a significant predictor of obesity, demonstrating high diagnostic accuracy. The complex interactions among these adipokines underscore the necessity for comprehensive obesity management strategies.